Strategi Pemberdayaan Ekonomi melalui Budidaya Ikan Air Tawar dalam Meningkatkan Pendapatan Masyarakat di Desa Sei Ijum Raya Kabupaten Kotawaringin Timur - Rahmah Rahmah; Rinto Alexandro; Hidayati Hidayati (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to identify the success of freshwater fish farming in increasing community income and to assess the economic impact of the community through freshwater fish farming on increasing community income in Sei Ijum Raya Village, East Kotawaringin Regency. This study starts from research preparation, data collection, data processing, to processing the results. The data collected are primary data and secondary data. Primary data is obtained through direct observation and interviews with freshwater fish farming business managers using a questionnaire and interview list. Secondary data is obtained from literature studies, related agencies, the Swadaya Service and other sources that can support this research. In the freshwater fish farming business in Sei Ijum Raya Village, the marketing strategy implemented includes sales to permanent collectors, local markets, and local collectors at varying prices, which still generate profits. The results of the study showed that income from freshwater fish farming reached IDR 30,000,000 per year, although it was still lower than the income of fish-ermen which averaged IDR 60,000,000 per year. The economic impact of this business increased by 50% per year, allowing farmers to meet the economic needs of their families. Although the community operates with their own capital and limited knowledge, significant harvest success and increasing market demand indicate that good management can increase yields. This study also found that the difference in success between farmers who have capital and those who do not have capital reached 30%, confirming the importance of access to capital in improving the economic welfare of the community